ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI BURNOUT PADA PERAWAT : STUDI LITERATURE - Salma Fuady; Pramesti Dewi; Indri Heri Susanti (Jurnal Cakrawala Ilmiah, 2022)
Background: Work fatigue is still a serious problem, burdening the service system, including health workers. Maslach and Schaufeli define job burnout as physical or emotional exhaustion that leads to a negative self-concept, inattention, and poor work attitude. Objective: The purpose of this study is to analyze the factors that affect nurses' work fatigue. Methods: The source of the literature study was a systematic search of the Google Schoolar computerized database, as many as 15 journals. Results: Factors causing nurse burnout are demographic factors, including working hours and marital status. Personal factors include work pressure, workload, personality type, control points and self-efficacy. Organizational factors include social support and work motivation.